A Bibliometric Analysis and Visualization of Fractional Order Research in China over Two Decades (2001–2020). (13th August 2021) - Yang, Yunfei; Lv, Ke; Xue, Jian; Huang, Xi
Abstract : Fractional order research has interdisciplinary characteristics and has been widely used in the field of natural sciences. Therefore, fractional order research has become an important area of concern for scholars. This paper used 2854 literatures collected from China National Knowledge Infrastructure (CNKI) database from 2001 to 2020 as the data source and used bibliometrics and two visualization methods to conduct bibliometric analysis and visualization research on China's fractional order research. To begin with, this paper analyzed the time series distribution of publications, the distribution of research institutions, the author cooccurrence network, the distribution of important journals, and the distribution of important literature, which explained the research status of the fractional order. Furthermore, this paper used VOSviewer software to analyze the clustering and density distribution of the fractional order research keywords, which revealed the hotspots of the fractional order research. Finally, with the help of CiteSpace software, the burst keywords were analyzed to further explore the frontiers of fractional order research. This paper systematically reveals the research status, research hotspots, and research frontiers of China's fractional order research, which can provide certain theoretical and practical references for related follow-up researchers.